Pengaruh Media Kartu Kata Bergambar terhadap Keterampilan Membaca Permulaan Siswa Kelas II SDN 07 Sungai Raya - Ariyani, Endang (Lembaga Yasin AlSys, 2023)
The use of media at the elementary school level is important. Given that the age of elementary school students is included in the concrete operational stage, the use of media is expected to optimize learning activites. The attractiveness of a media can be the attraction of the media itself. Utilization of media in learning can help inmprove student concentration. The word card is a media in the from of a card in which there are pictures and words that match the picture. Word cards with pictures will make it easier to read the beginning. Word card media is very fun learning and also makes children creative and easy to read. The success of reading learning activities through word cards is proven to improve reading in children. The purpose of this study was to determine the effect of using word card on the learning outcornes of early reading for grade II student at SDN 07 Sungai Raya. This study uses research and development methods (Research and Development) by adapting the Sukmadinata model, the method used is document recording and interviews which are then analyzed using qualitative descriptive methods.